109k views
1 vote
P=-4t+24p=3t-18solve the system using the subsition method if there is no solution put no solution if there is infinite solutions put infinite

User Noxxys
by
4.8k points

1 Answer

5 votes

Given system is


\begin{gathered} 3t-18=p \\ -4t+24=p \end{gathered}

Substuting


p=3t-18

in the second equation, we have,


\begin{gathered} -4t+24=3t-18 \\ -4t-3t=-18-24 \\ -7t=-42 \\ t=6 \end{gathered}

Then,


\begin{gathered} p=3(6)-18 \\ =0 \end{gathered}

So, the solution is

p=0,t=6

User HardQuestions
by
4.7k points